Eighteenth-Century Russia. - Chrissidis, Nikolaos (2008)
Worked on a book and wrote and presented several paper on eighteenth century Russia.
Keywords: dept.his; faculty_collection; sabbatical_report

The Cassock Does Not a Monk Make. Or Does It? Fake and Real Monks from the Orthodox East in the Russian Empire (19th — Early 20th Сentury) - Chrissidis, Nikolaos (Istoriya, 2023)
Monastic tonsure of citizens of the Russian Empire abroad became a particularly complex issue during the latter half of the nineteenth century, when Mt. Athos became a favorite destination of those interested in assuming the monastic habit outside the empire. The Russian authorities sought to control and regulate such tonsures by establishing procedures for checking their validity, and by ruling out automatic recognition of them in the empire. Individuals who were tonsured as monks abroad manipulated or tried to manipulate such regulations in order to facilitate travel back and forth from the Russian Empire for their own purposes. The result was that the real and apparent ambiguities that such rules allowed for were exploited by both state authorities and by real or fake monks themselves. The essay seeks to offer some perspectives on this phenomenon by focusing on four cases preserved in archival records. © 2023 Ltd "Integration: Education and Science". All rights reserved.
Keywords: Mount Athos; St. Panteleimon Monastery; dept.his; fake monks; monasticism; peer-reviewed; tonsures abroad

Aspects of Greek-Russian Relations in the Early Modern and Modern Periods (17th-20th Centuries) - Chrissidis, Nikolaos (Annuaire de l'École pratique des hautes études (EPHE), Section des sciences religieuses. Résumé des conférences et travaux, 2023)
This series of four presentations sought to examine case studies of Greek-Russian relations in the early modern and, mostly, modern period. In the choice of topics, I was guided by two considerations: first, I sought to highlight topics that, to my mind, have not yet attracted the attention they deserve in historiography. For example, although alms collections in the Russian Empire in the early modern period have been discussed repeatedly, this has not been the case until quite recently for t...
Keywords: Christianisme orthodoxe; Histoire des chrétiens d’Orient (XVIe-XXIe siècle); dept.his

Edification through the memory of sins - Chrissidis, Nikolaos A. (Canadian-american Slavic Studies, 2018)
The article explores the practical uses of Eastern Orthodox indulgences as certificates of absolution with a dual function (as mnemonic tools and as public certificates of good standing with the church) in the early modern period. © KONINKLIJKE BRILL NV, LEIDEN, 2018
Keywords: Eastern Orthodox indulgences; Eastern Orthodox penitential practices; Mese katastasis ton psychon; Patriarch Dositheos of Jerusalem; Purgatory; Synchorochartia; dept.his; peer-reviewed

The World of Eastern Orthodoxy - Chrissidis, Nikolaos A. (The Oxford Handbook of Early Modern European History, 1350-1750, 2015)
The chapter traces the development of Orthodoxy by focusing on the Ecumenical Patriarchate of Constantinople and the Russian Orthodox Church in the early modern period. It is based on the premise that in both cases Orthodoxy faced three main challenges: imperial/political, intellectual, and financial. In both the Ottoman and the Russian empires, the Orthodox Church played important roles in the political, administrative, cultural, economic, ideological, and social lives of the Orthodox believers. Orthodoxy usually provided legitimizing ideological support to state authority, was forced to reckon with Western cultural and theological trends, and also proactively defended its economic interests. For most of the period, the Ecumenical Patriarchate and the Russian Orthodox Church maintained constant contacts, even in the face of mutual suspicions of each other’s motives. The chapter argues that early modern Orthodoxy proved adaptive, developed over time, and withstood the challenges it faced, ultimately keeping its symbolic capital largely intact.
Keywords: dept.his

The russian holy synod and the greeks: Reconsidering greek-russian relations in the early modern period (16th–18th centuries) - Chrissidis, Nikolaos A. (Canadian-American Slavic Studies, 2020)
The article first surveys Greek interpretations of the creation of the Russian Holy Synod by Peter the Great. It provides a critical assessment of the historiographical paradigm offered by N.F. Kapterev for the analysis of Greek-Russian relations in the early modern period. Finally, it proposes that scholars should focus on a Greek history of Greek-Russian relations as a complement and possibly corrective to the Kapterev paradigm. © verlag ferdinand schöningh, 2020.
Keywords: Aleksander stourdza; Greek-russian relations; Konstantin oinonomos; Nikolai kapterev; Peter the great; Russian holy synod; dept.his; peer-reviewed

An Academy at the Court of the Tsars: Greek Scholars and Jesuit Education in Early Modern Russia - Chrissidis, Nikolaos A. (NIU Press, 2015)
Keywords: 17th century; 17th century; Education, Higher; 17th century; Greeks; Education; History; History; Jesuits; Leichoudēs, Iōannikios, 1633-1717; Leichoudēs, Sōphronios, 1652-1730; Moskovskai︠a︡ slavi︠a︡no-greko-latinskai︠a︡ akademii︠a︡; Moscow; Russia; Russia (Federation); dept.his; faculty_collection

Religion and Identity in Russia and the Soviet Union A Festschrift for Paul Bushkovitch - Chrissidis, Nikolaos A. (Slavica Publishers, Slavica, 2011)
Keywords: Bushkovitch, Paul; Nationalism; History; Christianity and politics; History; Identity (Psychology); History; Nationalism; History; Soviet Union; Politics and government; Politics and government; Russia; Religious aspects; Russia; Russkai͡a pravoslavnai͡a t͡serkovʹ; National characteristics, Russian; Soviet Union; dept.his; faculty_collection

A cartel that lasts for centuries: the case of the eastern orthodox church indulgences - Axarloglou, Kostas; Cabolis, Christos; Chrissidis, Nikolaos A (DUTH Research Papers in Economics, 2012)
Keywords: dept.his